The cat owner's manual - Allan, Eric (Gramercy Books,Distributed by Random House Value Pub., 1997)
This work explains how to care for and enjoy your cat. It contains all you need to know about living with a cat, cats who spend their lives indoors, first aid, nutrition, behaviour, reproduction, infectious diseases, and skin and coat